Ovarian Hormone Deprivation Reduces Oxytocin Expression in Paraventricular Nucleus Preautonomic Neurons and Correlates with Baroreflex Impairment in Rats - De Melo, Vitor U.; Saldanha, Rayssa R. M.; Dos Santos, Carla R.; De Campos Cruz, Josiane; Lira, Vitor A.; Santana-Filho, Valter J.; Michelini, Lisete C. (Frontiers in Physiology, 2016)
The prevalence of cardiovascular diseases including hypertension increases dramatically in women after menopause, however the mechanisms involved remain incompletely understood. Oxytocinergic (OTergic) neurons are largely present within the paraventricular nucleus of the hypothalamus (PVN). Several studies have shown that OTergic drive from PVN to brainstem increases baroreflex sensitivity and improves autonomic control of the circulation. Since preautonomic PVN neurons express different types of estrogen receptors, we hypothesize that ovarian hormone deprivation causes baroreflex impairment, autonomic imbalance and hypertension by negatively impacting OTergic drive and oxytocin levels in pre-autonomic neurons. Here, we assessed oxytocin gene and protein expression (qPCR and immunohistochemistry) within PVN subnuclei in sham-operated and ovariectomized Wistar rats. Conscious hemodynamic recordings were used to assess resting blood pressure and heart rate and the autonomic modulation of heart and vessels was estimated by power spectral analysis. We observed that the ovarian hormone deprivation in ovariectomized rats decreased baroreflex sensitivity, increased sympathetic and reduced vagal outflows to the heart and augmented the resting blood pressure. Of note, ovariectomized rats had reduced PVN oxytocin mRNA and protein expression in all pre-autonomic PVN subnuclei. Furthermore, reduced PVN oxytocin protein levels were positively correlated with decreased baroreflex sensitivity and negatively correlated with increased LF/HF ratio. These findings suggest that reduced oxytocin expression in OTergic neurons of the PVN contributes to the baroreflex dysfunction and autonomic dysregulation observed with ovarian hormone deprivation.